Advances in Glucose-Responsive Drug Delivery Systems: Revolutionizing Diabetes Management through Intelligent Therapeutics - K. Barath,; Farhath Sherin,; N. Damodharan, (The Bioscan, 2025)
Diabetes mellitus is a widely spread chronic disease that is associated with poor insulin production or response and requires a consistent follow-up and supplemental doses of insulin. Conventional modes of delivery, in typography subcutaneous injections, are reported to cause distress and in some cases poor glycemia control. Present progress in the field of glucose- controlled insulin delivery has introduced encouraging options in the use of intelligent biomaterials that adapt insulin delivery to ongoing changes in glucose. The most recent advances in glucose-responsive drug delivery are reviewed through enzymatic-based technologies such as glucose oxidase-based hydrogel carriers and nanoparticles, protein carriers like concanavalin A, and protein-free carriers including phenylboronic-acid-based hydrogel carriers and acetylated dextran nanoparticles. They are focused on their glucose sensing mechanism, efficiency in encapsulation of insulin, release and their adaptability to be administered either by injection or orally. The possible combination of digital health, closed- loop artificial pancreas, and microneedle patches are also discussed, which are expected to imitate the insulin secretion process in vivo, provide patient comfort, and have fewer chances of hypoglycemia events and hyperglycemia. Whereas the preclinical results are promising, long-term biocompatibility, effective in-vivo responsiveness, and manufacturing in a scalable manner pose as primary tasks. Future applications are the personal and precision medicine to benefit with artificial intelligence, big data analytics, and 3D printing of a personalized formulation. The combination of these innovations seems to indicate a groundbreaking transition to patient-centric and more effective diabetes care.